Reviewing coastal culture and traditions for English teaching materials - Warouw, Maya Pinkan; Ginting, Elvy Like; Tondo, Henry Fanny (Institute of Advanced Engineering and Science, 2024)
Women’s empowerment can be encouraged via English teaching and teaching materials can be utilized to strengthen gender equality and women’s empowerment, particularly for students from coastal areas pursuing higher education at universities. This research aims to determine how English language teaching (ELT) materials in universities can be adapted and incorporated into English instruction from the perspective of female students from coast. The data for this study were acquired using a qualitative technique, which included the distribution of questionnaires and interviews with female students from coastal locations. The information gathered from the questionnaire was mostly demographic. In the meanwhile, interviews were held to collect thoughts from participants on coastal traditions and cultures that might be included into teaching materials. The findings reveal a clear correlation between individuals’ perspectives and their experiences shaped by traditions and cultural heritage of coastal regions. Female participants highlight the depth of coastal culture, it is interaction with the environment, the crucial role of women in preserving traditions, and the desire for representation in university-level English teaching materials. These insights, derived from the experiences and viewpoints of female students in a coastal setting, extend beyond their locale, offering valuable lessons for English learning approaches in diverse coastal communities